The theory of dimensional balance of needs. Issue 2 (4th March 2017) - Poveda, Cesar A.
ABSTRACT: Sustainability has been a popular heuristic concept used to describe the necessity for achieving a point of balance between social, economic, and environmental needs for the purpose of securing the survival of humankind and the planet. With the objective of meeting the interests of something or someone, the definition of the term has been subject to interpretation, generating confusion, and increasing the vagueness already embedded in the terminology. Revisiting sustainability definitions and departing from the roots of the issue, the theory of dimensional balance of needs proposes a framework for sustainability to attain full theoretical status. This article will explore and develop a theory for sustainability to achieve a three-dimensional balanced status in which the sustainability environment system (SES) is integrated by the dimensional environment subsystem (DESS) and the stakeholder environment subsystem (SESS). The DESS includes three dimensions representing the social, economic, and environmental needs and the three dimensional salience of needs (i.e. human well-being, economic development, and environmental protection). By balancing one or more dimensional salience of needs, the DESS enters into different balanced states, which are presented as propositions, and the balance of the three dimensional salience of needs represents a balanced sustainability state that has been able to integrate and balance internal and external factors – the three-dimensional integrated and balanced state that stakeholders are interested in sustaining as it signifies the needs have been met.